Association of anthropometric indices with rs9939609 FTO gene polymorphism among overweight/obese women with breast cancer: a case-control study - Naqeeb, Huma; Sehar, Bismillah; Siraj, Sami; Almajwal, Ali Madi; Hajira, Bibi; Faris, MoezAlIslam; AlBlooshi, Sharifa; Alsubaie, Ali Saad R.; Safdar, Mahpara; Alam, Iftikhar; Zeb, Falak (Frontiers in Nutrition, 2025)
Background/objectivesFat mass and obesity associated (FTO) gene and anthropometric measurements might be associated with breast cancer (BC) risk. This study aimed to assess the interactions between single nucleotide polymorphism (SNP) rs9939609 of the FTO gene, anthropometric indices, and BC risk among pre- and post-menopause women with overweight/obesity in Pakistan.MethodsThis retrospective case–control study conducted on a convenience sample of 200 women divided into two groups: a case group comprised of 100 women diagnosed with BC, and control group comprised of 100 (age and menopausal status matched healthy women). Physical activity was assessed using validated questionnaire. Data on body mass index (BMI, kg/m2), waist-to-hip ratio (WHR, cm), sociodemographic, and blood samples were collected from both groups. The rs9939609 FTO gene polymorphism was genotyped using the tetra-primer amplification refractory mutation system polymerase chain reaction and Sanger sequencing. Multiple regressions were presented as adjusted odds ratios (OR) and their respective confidence intervals (95% CI).ResultsThe FTO rs9939609 T > A polymorphism showed a significantly higher frequency of the homozygous AA genotype in BC patients compared to healthy controls (22% vs. 13%, p < 0.05). The odds ratio for BC was 2.4 (CI = 1.09–5.3, p < 0.05), indicating that women with the AA genotype were more susceptible to BC compared to those with the wild-type TT genotype. Additionally, BC patients exhibited significantly higher BMI (27 ± 4.0 vs. 25 ± 3.4, p < 0.05) and WHR (0.88 ± 0.06 vs. 0.85 ± 0.08, p < 0.05) compared to healthy controls. These findings suggest a significant association between the FTO rs9939609 AA genotype, obesity, and BC risk.ConclusionFTO gene polymorphism may be implicated in the etiopathogenesis of BC, both in FTO pre- and post-menopause women diagnosed with overweight/obesity. Future cohorts are required to confirm the association between the FTO gene and BC in obese women and to identify the underlying biological mechanisms.